Level and speed of acquisition integration and their effects on technological performance - Liang-Hung, Lin; Yu-Ling, Ho (Journal of strategy and management, 2021)
PurposeThis study concerns two aspects of the integration process critical for the success of acquisitions: (1) levels of human integration and task integration and (2) speeds of human integration and task integration. The purpose of this study is to examine the interaction effects of human/task integration level and human integration speed advantage on acquisition performance.Design/methodology/approachThis study collected data of companies in the Taiwanese high-tech industries at the financial, organizational and industrial levels to examine the proposed hypotheses. Corporate financial and patent data were collected from the Taiwan Securities and Futures Commission databases and the Intellectual Property Office (IPO) databases. The organizational level data were collected from 142 publicly traded related acquisitions from 2008 to 2009 in the Taiwanese high-tech industries.FindingsThe results show that (1) a high level of human integration positively affects technological performance; (2) the interaction term of human integration level and human integration speed advantage (i.e., relatively faster human integration coupled with slower task integration) positively affects technological performance; and (3) the interaction term of task integration level and human integration speed advantage positively affects technological performance.Originality/valueThe originality of this study lies in advancing our understanding of how complex interactions between human/task integration level and human integration speed advantage affect acquisition performance.